KEPEMIMPINAN PENDIDIKAN GLOBAL BERBASIS BUDAYA: TANTANGAN DAN INOVASI DI SEKOLAH DASAR - Weni Yulastri; Salsabila; Makhdalena; Febrio Rozalmi Putra; Gusmal Hendra; Yustina (STKIP Subang, 2025)
This research aims to analyze the issues of culture-based global education leadership found at SDN 51 Kuranji and to formulate appropriate approaches and innovations to address them. The study employs a qualitative approach using literature review methods and field observations. The observations reveal four main issues: the mismatch between the national curriculum and the local cultural context, gaps in access and resources, language barriers in learning, and the lack of educators' understanding of the concept of global leadership. In-depth literature analysis from various national and international journals supports that innovations such as the development of multicultural curricula, cross-cultural training, utilization of technology, and culture-based transformational leadership models can be solutions.This study concludes that global educational leadership rooted in local cultural values is key in building an inclusive and adaptive education system to global challenges.